Management of UEIIA/UFSM in Covid-19 times: listening, dialogue and rupture (Olhar de Professor, 2021)
This paper aims to show some of our actions as a management team in the Unit of Early Childhood Education Ipê Amarelo - UEIIA/UFSM (RS) - concerning the social distancing to help prevent the spread of Covid-19. These actions include discussing, analysing and proposing what is possible to do in this moment with actual subjects through a closer look, sensitive listening, participation, and constant dialogue with all, ensuring UEIIA’s identity. Drawing on the national law of Early Childhood Education (BRASIL, 2009; CAMPOS; ROSEMBERG, 2009) and reference frames in the field of Early Childhood Education based on listening and welcoming (RINALDI, 2014; STACCIOLI, 2013), we have considered that this is the time for new ways of social life, dialogue, enhance of relations with a possible future, a new institutional culture.
Keywords: Management. Early Childhood Education. Covid-19.